Safety and efficacy of retrograde intrarenal surgery for the treatment of renal stone in solitary kidney patients. (15th October 2018) - Lai, Dehui; Chen, Meiling; He, Yongzhong; Li, Xun; Wan, Shawpong
Abstract: Purpose: We present our experience of retrograde intrarenal surgery (RIRS) for the treatment of renal stones in patients with solitary kidneys and evaluate the safety and efficacy of this treatment modality. Materials and methods: Between March 2011 and July 2015, the clinical records of 60 patients with renal stones in solitary kidneys who underwent RIRS were retrospectively reviewed. Demographic characteristics, preoperative urinary culture, blood biochemistry, stone location, and surface area were documented. The final stone-free rates (SFRs) were assessed one month after the last treatment session by computed tomography (CT). Preoperative, operative, and postoperative parameters were analyzed. Serum creatinine (Scr) and glomerular filtration rate (GFR) were measured preoperatively, one month postoperatively, and at each follow-up visit. Results: The mean stone burden was 628 ± 27.2 mm 2 (range 301–1199). The mean operative time was 84.4 ± 21.3 min (range 40–115). The mean drop in postoperative hemoglobin was 0.6 ± 0.21 g/dL (range 0.1–0.7). Twelve patients (20%) required second-stage RIRS for residual stones. The SFRs after the single and second procedures were 80% and 95%, respectively. The mean preoperative Scr level was 111.6 ± 45.59 μmol/L, and the mean postoperative Scr level was 96.7 ± 34.12 μmol/L. The change was statistically significant ( p = .008). The same findings were observed for GFR. The mean preoperative GFR was 65.04 ± 25.37 ml/min, and the mean postoperative GFR was 76.89 ± 27.2 ml/min ( p = .023). Minor complications occurred in nine patients (15%). One patient experienced septic shock and acute renal failure due to steinstrasse. This patient required hemodialysis and percutaneous nephrostomy drainage. One patient developed perirenal abscess and was treated with percutaneous drainage. Conclusion: RIRS is a safe and effective procedure for the treatment of renal stones in patients with solitary kidneys. RIRS did not adversely affect renal function at either the short-term or the long-term follow-up.